Varicose veins due to anomalous arteriovenous communicants in the lower limbs. - Matteucci, Pablo; Lucinschi, Alicia; Figueredo, Mario; Alvarez, Carmelo; Ferreira, Ciro (Cirugía del Uruguay, 1989)
Varicose veins due to anomalous arteriovenous communicants in the lower limbs are entities that should be set apart from the classical Klippel-Trenaunay-ParkerWeber syndromes with very definite pathological disorders. They tend to appear in young patients, and one of their features is that they expose patients tosurgical failures and recidives if they are not correctly treated. Authors make clinical considerations on this disease and present tour cases, all of them clearly doccumented by arteriography.